On Writing Well: The Classic Guide to Writing Nonfiction (6th ed.). - Jack Sperbeck (Journal of Applied Communications, 1998)
A review of On Writing Well: The Classic Guide to Writing Nonfiction (6th ed.), by William Zinsser.